2015
DOI: 10.1080/21645515.2015.1034916
|View full text |Cite
|
Sign up to set email alerts
|

Intention of nurses to receiving influenza vaccination before the 2013–14 season

Abstract: A study was conducted to determine the influenza vaccination uptake rate of nurses in Hong Kong after the pH1N1 epidemic, and examine their intention for vaccination before the next influenza season. Questionnaires in Chinese with multiple choice responses were delivered by post through 4 nurses organizations. The following were explored: intentions and reasons for vaccination in the forthcoming season; perceptions of influenza outbreak risk; attitudes toward professional obligation and vaccination policies. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 22 publications
2
10
0
Order By: Relevance
“…First of all, results from the multiple stepwise logistic regressions showed that perceived susceptibility of influenza was the most significant factor of having received influenza vaccination in the last influenza season and intention to receive influenza vaccination in the coming influenza season. Findings are consistent with the previous studies, which indicated that those who did not receive the vaccination might not realize their own risk in getting influenza (Ajenjo et al., ; Clark et al., ; Hollmeyer et al., ; Maltezou et al., ; Wang et al., ). Findings support the notion that interventions to promote influenza vaccinations should highlight the risk of the nurses in contracting influenza as well as their potential sources of infection for their patients.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…First of all, results from the multiple stepwise logistic regressions showed that perceived susceptibility of influenza was the most significant factor of having received influenza vaccination in the last influenza season and intention to receive influenza vaccination in the coming influenza season. Findings are consistent with the previous studies, which indicated that those who did not receive the vaccination might not realize their own risk in getting influenza (Ajenjo et al., ; Clark et al., ; Hollmeyer et al., ; Maltezou et al., ; Wang et al., ). Findings support the notion that interventions to promote influenza vaccinations should highlight the risk of the nurses in contracting influenza as well as their potential sources of infection for their patients.…”
Section: Discussionsupporting
confidence: 91%
“…In fact, misconceptions about the vaccine and side effects have been widely reported among nurses despite their relatively high level of education and knowledge in the health‐related field. One study showed that 58% or more healthcare workers experienced side effects after vaccination and those “significant” side effects were associated with refusal of vaccination (Wang et al., ). Findings suggest that in addition to highlighting the importance and necessity of influenza vaccination, intervention efforts should be sought to clarify the myths or misconceptions of vaccination and to highlight the minimal time required for receiving influenza vaccination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this multiseason study of adults working in acute care hospitals in Canada, the odds ratio for influenza vaccine uptake increased exponentially with every additional year of influenza vaccine uptake over the previous three seasons. Similar findings have been illustrated in studies from the USA, Europe and China, suggesting that the individual perceptions associated with vaccine acceptance and refusal remain stable over several years. It is likely necessary to tailor immunization programs differently to reach HCW at all levels of uptake, from refusers to those accepting influenza vaccine intermittently to those vaccinated annually.…”
Section: Discussionsupporting
confidence: 85%
“…International guidelines stress the significance of this approach with recommendations of organizational strategies to immunize HCW annually [ 7 , 8 ]. However, the challenge in maintaining high vaccination coverage of HCW has been marked by unfavorably low compliance rates [ 9 , 10 ], and limited improvement by voluntary motivations through incentives and provision of free vaccine [ 11 , 12 ]. The use of mandatory or regulatory policy has consequently gained popularity and has been implemented in organizations based on the premise of indirect patient benefits [ 13 , 14 ], while the evidence for this as a primary driver for HCW programs remains contentious [ 15 ].…”
Section: Introductionmentioning
confidence: 99%